Which Problems to Solve? Online Knowledge Sharing and Attention Allocation in Organizations - HAAS, Martine R. (Institutional Knowledge at Singapore Management University, 2015)
Why do individuals allocate attention to specific problems in organizations? Viewing online knowledge sharing as a matching process between knowledge providers and problems, we examine attention allocation in the context of an online community within which knowledge providers respond to problems posted by other organization members. We argue that knowledge providers are more likely to allocate attention to solving problems that more closely match their expertise, but that decisions to allocate attention are also influenced by problem characteristics such as length, breadth, and novelty, as well as by problem crowding. Analyzing 1,251 realized matches and 12,510 nonrealized matches among knowledge providers and problems posted over a 32-month period on an online discussion forum within a global engineering firm, we find evidence to support our claim that attention allocation is driven by the features of a particular provider–problem match, thereby shifting the discourse from knowledge provider–seeker relationships to knowledge provider–problem matches. The implications for theories of knowledge sharing, matching processes, and managerial attention are discussed.